Synthesis of 4-(3-oxo-3-phenylpropyl)morpholin-4-ium chloride analogues and their inhibitory activities of nitric oxide production in lipopolysaccharide-induced BV2 cells - Yoon, Sung Hwa; Lee, Eunhwa; Cho, Duk Yeon; Ko, Hyun Myung; Baek, Ha Yeon; Choi, Dong Kug; Kim, Eunha; Park, Ju Young (Bioorganic and Medicinal Chemistry Letters, 2021)
Based on our previous report that 3-morpholino-1-phenylpropan-1-one 2, one of the fluoxetine's simplified morpholino analogue, inhibited nitric oxide (NO) production, in this paper, various substituted benzene analogues with morpholine hydrochloride of 2 were synthesized and their inhibitory effects on NO production in lipopolysaccharide (LPS)-induced BV2 cells were tested. Among the synthesized compounds, 2-trifluoromethyl analogue 16n (IC50 = 8.6 μM) showed a significantly higher inhibitory activity than that of the parent compound 2a (IC50 > 50 μM) and suppressed NO production dose-dependently without cytotoxicity. Compound 16n also inhibited iNOS expression in LPS-induced BV2 cells at 2, 10 and 20 μM concentrations. These results suggest that compound 16n inhibited NO production by suppressing the expression of iNOS and can be used as a lead structure for developing new inhibitor of NO production.
Keywords: Animals; Cell Line; Chlorides; Dose-Response Relationship, Drug; Lipopolysaccharides; Mice; Molecular Structure; Morpholines; Nitric Oxide; Structure-Activity Relationship; 3-Morpholino-1-phenylpropan-1-one analogues; BV2 cell; NO production